73.4k views
5 votes
HELP PLEASE

problems 11 through 17​

HELP PLEASE problems 11 through 17​-example-1

1 Answer

3 votes

Answer:

Part 11) The vertex is the point (4,32)

Part 12) The vertex is the point (1,-5)

Part 13) The vertex is the point (-2,5)

Part 14) The vertex is the point (-1,-1)

Part 15) The vertex is the point (1,8)

Part 16) The vertex is the point (3,-26)

Part 17) The vertex is the point (-5,-32)

Explanation:

Part 11) we have


y=-x^2+8x+16

we know that

The quadratic equation written in vertex form is equal to


y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

Convert to vertex form


y=-x^2+8x+16

Factor -1


y=-(x^2-8x)+16

Complete the square


y=-(x^2-8x+16)+16+16


y=-(x^2-8x+16)+32

Rewrite as perfect squares


y=-(x-4)^2+32

The vertex is the point (4,32)

Part 12) we have


y=3x^2-6x-2

we know that

The quadratic equation written in vertex form is equal to


y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

Convert to vertex form


y=3x^2-6x-2

Factor 3


y=3(x^2-2x)-2

Complete the square


y=3(x^2-2x+1)-2-3


y=3(x^2-2x+1)-5

Rewrite as perfect squares


y=3(x-1)^2-5

The vertex is the point (1,-5)

Part 13) we have


y=-2x^2-8x-3

we know that

The quadratic equation written in vertex form is equal to


y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

Convert to vertex form


y=-2x^2-8x-3

Factor -2


y=-2(x^2+4x)-3

Complete the square


y=-2(x^2+4x+4)-3+8


y=-2(x^2+4x+4)+5

Rewrite as perfect squares


y=-2(x+2)^2+5

The vertex is the point (-2,5)

Part 14) we have


y=2x^2+4x+1

we know that

The quadratic equation written in vertex form is equal to


y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

Convert to vertex form


y=2x^2+4x+1

Factor 2


y=2(x^2+2x)+1

Complete the square


y=2(x^2+2x+1)+1-2


y=2(x^2+2x+1)-1

Rewrite as perfect squares


y=2(x+1)^2-1

The vertex is the point (-1,-1)

Part 15) we have


y=-5x^2+10x+3

we know that

The quadratic equation written in vertex form is equal to


y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

Convert to vertex form


y=-5x^2+10x+3

Factor -5


y=-5(x^2-2x)+3

Complete the square


y=-5(x^2-2x+1)+3+5


y=-5(x^2-2x+1)+8

Rewrite as perfect squares


y=-5(x-1)^2+8

The vertex is the point (1,8)

Part 16) we have


y=3x^2-18x+1

we know that

The quadratic equation written in vertex form is equal to


y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

Convert to vertex form


y=3x^2-18x+1

Factor 3


y=3(x^2-6x)+1

Complete the square


y=3(x^2-6x+9)+1-27


y=3(x^2-6x+9)-26

Rewrite as perfect squares


y=3(x-3)^2-26

The vertex is the point (3,-26)

Part 17) we have


y=x^2+10x-7

we know that

The quadratic equation written in vertex form is equal to


y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

Convert to vertex form


y=x^2+10x-7

Complete the square


y=(x^2+10x+25)-7-25


y=(x^2+10x+25)-32

Rewrite as perfect squares


y=(x+5)^2-32

The vertex is the point (-5,-32)

User Justdvl
by
5.5k points